Midwest marvels : roadside attractions across Iowa, Minnesota, the Dakotas, and Wisconsin - Dregni, Eric, 1968- (University of Minnesota Press, 2006)
Regional travel expert Eric Dregni takes the reader on an off-center tour of the bizarreand the beautifulacross Iowa, Minnesota, the Dakotas, and Wisconsin, from the Corn Palace to the world's tallest structure: a TV tower jutting nearly a half mile into the sky. Complete with descriptions, driving directions, and photographs, Midwest Marvels is a must-have for everyone from armchair travelers to road warriors.